Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.cell.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The v-ATPase V 0 Subunit a1 Is Required for a Late Step in Synaptic Vesicle Exocytosis in Drosophila

Abstract: The V(0) complex forms the proteolipid pore of an ATPase that acidifies vesicles. In addition, an independent function in membrane fusion has been proposed largely based on yeast vacuolar fusion experiments. We have isolated mutations in the largest V(0) component vha100-1 in flies in an unbiased genetic screen for synaptic malfunction. The protein is only required in neurons, colocalizes with markers for synaptic vesicles as well as active zones, and interacts with t-SNAREs. Loss of vha100-1 leads to vesicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
356
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(375 citation statements)
references
References 49 publications
13
356
4
1
Order By: Relevance
“…Indeed, further studies revealed that the a1 subunit of the V 0 sector is a crucial factor in vacuole fusion, acting downstream of trans-SNARE pairing (60,61). Consistently, the V 0 sector was involved in vesicle fusion during exocytosis in neurons (62,63). More recently, studies with zebrafish microglia established that the a1 subunit mediates fusion independently of its proton pump activity (64).…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, further studies revealed that the a1 subunit of the V 0 sector is a crucial factor in vacuole fusion, acting downstream of trans-SNARE pairing (60,61). Consistently, the V 0 sector was involved in vesicle fusion during exocytosis in neurons (62,63). More recently, studies with zebrafish microglia established that the a1 subunit mediates fusion independently of its proton pump activity (64).…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, the vesicle fusion and its apparatus must be more or less similar among different types of neurons [63][64][65][66][67]. In any case, however, the evidence for somatic or dendritic release of DA through ATP6V0C in non-dopaminergic neurons or glia is likely to be very weak at this moment.…”
Section: Overview Of Gene or Cell Transplantation Therapy For Neurodementioning
confidence: 99%
“…It is possible to postulate another mechanism whereby a complex of proteolipid channels involved in SNARE fusion may effectively secrete DA from DA-accumulating cells in the striatum, as described in yeast and Drosophila [7,65,66].…”
Section: Overview Of Gene or Cell Transplantation Therapy For Neurodementioning
confidence: 99%
“…2,[14][15][16] Recently, it has also been shown that the V-ATPase a-subunit directly assembles with proteins that are not part of the V-ATPase complex including: (i) aldolase B, 17,18 (ii) phosphofrucktokinase-1, 19,20 (iii) calmodulin, 21 and (iv) t-SNARES syntaxin and SNAP-25. 22 However, the mechanisms and molecular details of interactions with these proteins remain poorly understood, mainly due to the lack of a high-resolution structure of the a-subunit and the absence of studies designed for mapping interaction sites on both the a-subunit and its associated proteins.…”
Section: Introductionmentioning
confidence: 99%